1996
DOI: 10.2307/1131752
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers' Understanding of Plan and Oblique Maps: The Role of Geometric and Representational Correspondence

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 14 publications
4
39
0
Order By: Relevance
“…What's a map?" (Liben & Yekel, 1996, p. 2786, over half were able to explain maps as archives of location information (e.g., "Where things are" and "Things with different countries"), as navigation tools (e.g., "Something to get around places" and "Something if you get lost, it helps you to get somewhere . .…”
Section: Maps As Tools Within and Beyond Geographymentioning
confidence: 99%
See 3 more Smart Citations
“…What's a map?" (Liben & Yekel, 1996, p. 2786, over half were able to explain maps as archives of location information (e.g., "Where things are" and "Things with different countries"), as navigation tools (e.g., "Something to get around places" and "Something if you get lost, it helps you to get somewhere . .…”
Section: Maps As Tools Within and Beyond Geographymentioning
confidence: 99%
“…The latter tasks, however, typically place only very minimal demands on children's understanding of symbols because there is usually a unique symbol for each unique referent. When representation tasks include symbols that are less iconic or include multiple instances of the same symbol, performance is significantly worse (see Blades & Spencer, 1994;Liben & Yekel, 1996). In such cases, children may need to rely on spatial understanding to disambiguate which of two or more identical symbols stands for a particular referent.…”
Section: Developing Representational Map Understandingmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating children's map use in spatial search tasks have shown that preschoolers have great difficulties (Liben & Yekel, 1996), and their accuracy to locate targets develops considerably (Frick & Newcombe, 2012;Vasilyeva & Huttenlocher, 2004). However, if task requirements are low, even 3-year-olds succeed in using metric information from small-scale maps (Huttenlocher, Newcombe, & Vasilyeva, 1999).…”
Section: Introductionmentioning
confidence: 99%